Therapeutic Efficacy of Ultrasound-Guided High-Voltage Long-Duration Pulsed Radiofrequency for Pudendal Neuralgia. (31st July 2021) - Ji, Feng; Zhou, Shuzhuan; Li, Caixia; Zhang, Yongyan; Xu, Hua
Abstract : Pudendal neuralgia (PN) is a complex disease with various clinical characteristics, and there is no treatment showing definite effectiveness. This study is aimed at evaluating the clinical efficacy of ultrasound-guided high-voltage long-duration pulsed radiofrequency (PRF) for PN. Two cadavers (one male, one female) were dissected to provide evidence for localization of the pudendal nerve. Patients diagnosed as PN who failed or were intolerant in regular medication were screened for diagnostic local anesthesia block of the pudendal nerve before recruitment. Twenty PN patients were enrolled in this study. In the PRF procedure, the needle tip was inserted medially into the internal pudendal artery under ultrasound guidance. The position of the PRF needle tip was then adjusted by the response of the pudendal nerve to the electrical stimulation within the pudendal area (42°C, a series of 2 Hz, and 20 ms width pulses that lasted for 900 s). Alleviation of pain was assessed by the visual analogue scale (VAS) and sitting time pretreatment and on 7 d, 14 d, 1 m, 2 m, 3 m, and 6 m posttreatment in outpatient follow-up or by telephone interview. Two patients were lost due to intervention-irrelevant reasons. Patients showed significantly decreased VAS scores on 7 d after RFP, compared with pretreatment status (7.0 ± 0.9 vs. 3.2 ± 1.7, P < 0.001 ). The efficacy remained steady till the end of 6 months, with a final remission rate of 88.9%. Sitting time also significantly lengthened following PRF (7 d, 14 d, 1 m, 2 m, 3 m, and 6 m vs. pretreatment, all P < 0.05 ). Only short-term ipsilateral involuntary convulsion of the lower extremity was reported in one patient, who recovered within 12 h. Six patients were treated with nonsteroidal drugs for a short time. All patients stopped taking medication finally. In conclusion, the ultrasound-guided high-voltage long-duration PRF approach not only reduced the pelvic pain caused by PN but also improved the quality of life by extending sitting time without nerve injury.